1997
DOI: 10.1021/jf960645b
|View full text |Cite
|
Sign up to set email alerts
|

Whey Protein and Acetylated Monoglyceride Edible Coatings:  Effect on the Rancidity Process of Walnuts

Abstract: Whey protein isolate (WPI)-based coatings and distilled acetylated monoglyceride (AMG)-based coatings were evaluated for their ability to delay the oxidative rancidity of walnut pieces. Tocopherol (Toco) and ascorbyl palmitate (AP) were added to improve the performance of the coatings. Results indicate that, despite the low oxygen permeability and good continuity of the WPI coatings, there was no significant delay in the oxidative rancidity of walnuts. Shrinking of the WPI coating during drying, resulting in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 13 publications
2
22
0
1
Order By: Relevance
“…Therefore, CT had a positive effect on lipid protection against oxidation as an antioxidant. These results are consistent with the report of Mate, Frankel, and Krochta (1997), in which lipid oxidation was delayed when walnuts were coated with acetylated monoglyceride. From our results, SPI-coated walnuts were at similar levels of SPI/CMC-coated walnuts in terms of POV and TBA values.…”
Section: Effects Of Edible Coatings On Lipid Oxidation Of Walnutssupporting
confidence: 93%
“…Therefore, CT had a positive effect on lipid protection against oxidation as an antioxidant. These results are consistent with the report of Mate, Frankel, and Krochta (1997), in which lipid oxidation was delayed when walnuts were coated with acetylated monoglyceride. From our results, SPI-coated walnuts were at similar levels of SPI/CMC-coated walnuts in terms of POV and TBA values.…”
Section: Effects Of Edible Coatings On Lipid Oxidation Of Walnutssupporting
confidence: 93%
“…Heat denaturation of the proteins produces insoluble whey protein films as a result of formation of intermolecular disulfide bonds (Gennadios and others 1994;McHugh and others 1994). Whey protein-based films possess excellent oxygenbarrier property in low and intermediate RH, comparable to the synthetic polymer films (Maté and Krochta 1997;Trezza and Krochta 2002); they also are good grease barriers (Chan and Krochta 2001;Lin and Krochta 2003). Due to the hydrophilic nature of whey proteins, the films are not good moisture barriers.…”
Section: Protein-based Coatingsmentioning
confidence: 98%
“…Mehyar et al (2012) reported that edible coatings made of whey protein isolate, pea starch, and their combinations with carnauba wax (CW) were effective in preventing oxidative and hydrolytic rancidity of walnuts and pine nuts stored at 25°C, but were less effective at 50°C. Addition of tocopherol and ascorbyl palmitate in the edible coatings also had a positive effect in delaying the rancidity (Maté and Krochta, 1997).…”
Section: Walnut Meats and Oilmentioning
confidence: 94%
“…Hydroxypropyl starch composites are used for the preservation of candies, raisins, nuts and dates from oxidative rancidity (Arvanitoyannis et al , 1998). Whey protein isolate (WPI)-based edible fi lms have low O 2 permeability and can delay considerably O 2 uptake of dry roasted nuts (McHugh and Krochta, 1994;Maté and Krochta, 1997), thus delaying the rancidity process. These coatings could even provide a simpler, cheaper, and/or more recyclable package and continued protection of nuts after opening.…”
Section: Walnut Meats and Oilmentioning
confidence: 99%